Ablation behavior of (Hf–Ta–Zr–Nb–Ti)C high‐entropy carbide and (Hf–Ta–Zr–Nb–Ti)C–xSiC composites. Issue 10 (23rd June 2022) - Wang, Yichen; Yu, Duo; Yin, Jie; Zhang, Buhao; Zhang, Hangfeng; Liu, Xuejian; An, Yulong; Reece, Michael J.; Huang, Zhengren
Abstract: The ablation behavior of (Hf–Ta–Zr–Nb–Ti)C high‐entropy carbide (HEC‐0) was investigated using a plasma flame in air for different times (60, 90, and 120 s) at about 2100°C. The effect of SiC content on the ablation resistance of HEC– x SiC composites ( x = 10 and 20 vol%) was also studied. The linear ablation rate of HEC‐0 decreases with increasing ablation time, showing the positive role of the oxide layer with a complex composition. The linear ablation rate of HEC–10 vol% SiC (0.3 µm s −1 ) is only a 10th of that of HEC‐0, showing a significant improvement in ablation resistance, probably due to the formation of a protective oxide layer containing melted SiO2 and refractory Hf–Zr–Si–O oxides.